Filologia di un best seller. Sul Céline inedito - Mela, Giulia (L'ospite ingrato, 2022)
Guerre by Louis-Ferdinand Céline was published by Gallimard for the first time on May 5th, 2022. It is the first of an astonishing bunch of unpublished materials re-emerged in August 2021. It has been now a few weeks since its publication, and little debate has arisen about the dating of the manuscript which has been proposed by François Gibault and Pascal Fouché and seemingly generally accepted. In their view, Guerre would be a stand-alone novel, probably written in 1934, and therefore following the Voyage. Yet, a number of textual and extra-textual indicators and clues seem to indicate that the narrative of Guerre belonged to an earlier draft of the Voyage which the author removed from his final draft.